Air Power, NGOs, and Collateral Killings. Issue 2 (22nd January 2021) - Allen, Susan H; Bell, Sam R; Martinez Machain, Carla
Abstract: Air strikes have become an essential tool in major powers' military arsenals. Yet, despite the precise technology that air power represents, its use can also result in unintended killings. In this paper, we explore how air strikes affect civilian killings as collateral damage by third party interveners. In particular, we argue that this effect is conditioned by the presence of non-governmental civil society actors on the ground. We thus explore how air strikes affect civilian killings by government actors involved in conflicts and how civil society can diminish harm against civilian actors during aerial bombing campaigns. Our results suggest that air strikes may cause deaths through collateral killings. Yet, when air strikes occur in countries where human rights organizations are active, these civilian deaths may be mitigated.